1973
DOI: 10.1021/jo00958a004
|View full text |Cite
|
Sign up to set email alerts
|

Bridged azapolycyclic alcohols from intramolecular epoxide ring openings by amides

Abstract: An epoxide ring opening by an intramolecular nucleophilic attack of an amide group was utilized to synthesize 2-azanorbornan-6-ols and 2-azaadamantan-4-ols. The spectral identification of these compounds is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…This cascade sequence presumably proceeds by reduction of the nitrile, [61] followed by intramolecular epoxide opening by the resulting amine. [62] Of note, the authors observed that this cyclization is the first of its kind and, importantly, forges the [3.3.1] bicyclic moiety contained within the natural products structure. In addition, the opening of the epoxide elegantly provided a secondary alcohol functional group handle that could be used to later install the indole nucleus.…”
Section: Smith's Reductive Cyclization Approachmentioning
confidence: 95%
“…This cascade sequence presumably proceeds by reduction of the nitrile, [61] followed by intramolecular epoxide opening by the resulting amine. [62] Of note, the authors observed that this cyclization is the first of its kind and, importantly, forges the [3.3.1] bicyclic moiety contained within the natural products structure. In addition, the opening of the epoxide elegantly provided a secondary alcohol functional group handle that could be used to later install the indole nucleus.…”
Section: Smith's Reductive Cyclization Approachmentioning
confidence: 95%
“…Nach Behandlung von 85 mit H 2 und Rhodium auf Aluminiumoxid fand die gewünschte reduktive Cyclisierungskaskade statt, und das tricyclische Amin 87 wurde in 64 % Ausbeute erhalten. Die Kaskadensequenz verläuft vermutlich über die Reduktion des Nitrils61 und anschließende intramolekulare Epoxidöffnung des gebildeten Amins 62. Erwähnenswert ist, dass diese Cyclisierung die erste ihrer Art ist und auf effektive Weise die in der Struktur des Naturstoffs enthaltene [3.3.1]‐bicyclische Einheit aufbaut.…”
Section: Totalsynthesen Von (+)‐Scholarisin Aunclassified
“…Infrared spectrum (film) 3025, 2930, 1730, 1460, 1440, 1360, 1220, 1200, 1100, 1020, and 780 cm-1; nmr (CDC18) (TMS) 1.30-2.70 (11 H, m), 3.56 (3 H, s), 5.55 (2 H, m); mass spectrum (70 eV) m/e (rel intensity) 180 (10), 149 (11), 148 (60), 121 (10), 120 (10), 93, (11), 92 (10), 91 (17), 87 (11), 80 (12), 79 (100), 78 (70), 67 (12), 44 (42), 31 (23), 39 (12). ercdo-BicycIo[3.3.1]non-6-ene-3-carboxyhydrazide (4). A solution of 18 g (0.1 mol) of methyl ester 3 in 40 ml of ethanol was heated to reflux with 15 g (0.3 mol) of 99% hydrazine hydrate.…”
Section: Experimental Section18mentioning
confidence: 99%